The Hatfield-System versus the Weekly Undulating Periodised Resistance Training in trained males: Effects of a third mesocyle - Antretter, M.; Färber, S.; Immler, L.; Perktold, M.; Posch, D.; Raschner, C.; Wachholz, F.; Burtscher, M. (Journal of Human Sport & Exercise, 2019)
We recently demonstrated that recreationally strength trained men, randomly assigned to either a Hatfield-System (HAT) group or a weekly undulating periodisation (WUP) group showed significant increases in strength and power during only 2 mesocycles (6 weeks) without differences between groups. The questions arise, whether an additional mesocycle would further enhance strength and power equally or differently between groups. The same 26 strength trained men, assigned to the HAT (n = 13; age = 26.8 ± 7.2 years) or to WUP (n = 13; age = 29.2 ± 9.0 years) performed an additional mesocycle (3 weeks). Anthropometric measures and strength testing were performed again after finishing the third mesocycle and were then compared with the results recorded after the second mesocycle. Both the HAT and WUP groups made significant (p = 0.05) increases in strength and power - to approximately the same extent, again, without significant differences between groups. Thus, HAT and WUP are similarly effective over a nine-week training period, and the decision to use HAT or WUP depends on the preferences of the individual athlete.